A Classic Case of Maple Syrup Urine Disease and a Novel Mutation in the BCKDHA Gene - Alieh Mirzaee; Narges Pishva; Zohreh Karamizadeh; Jurgen Kohlhase; Shahnaz Purarian; Fariba Hemmati; Mostajab Razavi; Shiva Nasirabadi (Mashhad University of Medical Sciences, 2017)
Background: Maple syrup urine disease (MSUD) is an inherited branched-chain amino acid metabolic disorder caused by the deficiency in the branched-chain alpha-keto acid dehydrogenase (BCKD) complex. In MSUD, elevation of the branched-chain amino acids, such as alpha-keto acid and alpha-hydroxy acid, occurs due to the BCKDC gene deficiency, appearing in the blood, urine, and cerebrospinal fluid, which leads to neurological damage and mental retardation. MSUD phenotypically penetrates due to the mutations in the coding genes of four subunits of the BCKD complex, including the BCKDHA, BCKDHB, DBT, and DLD genes.Case report: We aimed to report the cases of three families whose children were affected by MSUD and presented with symptomatic features during the first week of birth, which were identified by mass spectrometry. DNA study was performed as a diagnosis panel containing four encoded BCKDC subunit genes.Conclusion: In the current study, DNA analysis and phenotypic manifestations indicated a novel mutation of c.143delT, p.L48Rfs*15 in the BCKDHA gene in a homozygous state, which is a causative mutation for the classic MSUD phenotype. Early diagnosis and neonatal screening are recommended for the accurate and effective treatment of this disease